2020
DOI: 10.1101/2020.06.11.147116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unilateral and Bilateral Subthalamic stimulation differently promote apathy: a translational approach

Abstract: Apathy is frequently reported in Parkinson's disease (PD) patients under subthalamic nucleus deep brain stimulation (STN-DBS). The prevailing clinical view for apathy following STN-DBS is the reduction of dopaminergic medication. However, few clinical reports and recent experimental data suggested the pathogenicity of bilateral STN-DBS on motivation, challenging the leading opinion. Here, we investigate whether bilateralism of STN-DBS influences apathy outcome after STN-DBS, combining pre-clinical and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…In FR or PR operant tasks, STN-DBS consistently decreased intravenous self-administration of addictive drugs (Rouaud et al, 2010;Wade et al, 2017). And while the effects of STN-DBS on motivation for natural rewards is more heterogeneous, the predominant effect of STN-DBS is also a decrease in rewards earned and consumed (Rummel et al, 2016) (Vachez et al, 2020b), but see (Rouaud et al, 2010;Vachez et al, 2020a). A decrease in reward seeking was also evident in extinction tasks, i.e., where STN-DBS operant responses were decreased in the absence of a previously available food pellet (Klavir et al, 2009).…”
Section: Stn-dbs Decreases Reward Seekingmentioning
confidence: 99%
See 3 more Smart Citations
“…In FR or PR operant tasks, STN-DBS consistently decreased intravenous self-administration of addictive drugs (Rouaud et al, 2010;Wade et al, 2017). And while the effects of STN-DBS on motivation for natural rewards is more heterogeneous, the predominant effect of STN-DBS is also a decrease in rewards earned and consumed (Rummel et al, 2016) (Vachez et al, 2020b), but see (Rouaud et al, 2010;Vachez et al, 2020a). A decrease in reward seeking was also evident in extinction tasks, i.e., where STN-DBS operant responses were decreased in the absence of a previously available food pellet (Klavir et al, 2009).…”
Section: Stn-dbs Decreases Reward Seekingmentioning
confidence: 99%
“…Another important factor to consider when interpreting the effects of STN-DBS on reward seeking is whether the stimulation is applied unilaterally (to a single hemisphere) or bilaterally. One set of studies performed under matched conditions from the same group reported that chronic unilateral STN-DBS during a FR1 task (Vachez et al, 2020a) did not recapitulate the sustained reward seeking deficit that occurred with chronic, bilateral stimulation (Vachez et al, 2020b). With the unilateral STN-DBS, the effect was only transient and lasted no more than 5 days.…”
Section: Unilateral Vs Bilateral Dbsmentioning
confidence: 99%
See 2 more Smart Citations